The human meibomian gland epithelial cell line as a model to study meibomian gland dysfunction. (October 2017) - Hampel, Ulrike; Garreis, Fabian
Abstract: The meibomian gland dysfunction (MGD) is the leading cause of dry eye disease (DED) throughout the world. The investigation of MGD lacks suitable in vivo and in vitro models. In 2010 a human meibomian gland epithelial cell line (HMGEC) was established, so far the only available meibomian gland cell line. The characterization of HMGEC is of major importance to clarify its suitability for studying the meibomian gland (patho)physiology in vitro. The current culture protocol and new concepts of HMGEC culture will be compared. Hormones are believed to be a key factor in meibomian gland dysfunction thus HMGEC responsiveness to hormone stimulation is crucial to elucidate the hormonal influence on the meibomian gland. This review will summarize current findings about HMGEC and discuss its role in the meibomian gland dysfunction research. Highlights: In vitro and in vivo models to study meibomian gland dysfunction are limited. The human meibomian gland cell line helps to study the (patho)physiology of the meibomian gland. The characterization and the optimization of culture conditions of the cell line is crucial for interpretation of results. The influence of various factors such as hormones has been identified.